1992
DOI: 10.1002/1097-0142(19920701)70:1<178::aid-cncr2820700128>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Types and causes of pain in cancer of the head and neck

Abstract: In a series of 25 patients with head dnd neck cancer who had severe pain, the type and cause of the pain were analyzed. There were two types of pain: nociceptive and nonnociceptive. Nineteen (76%) patients had nociceptive pain that could be subdivided into actual nociceptive pain (9 patients), nociceptive nerve pain (8 patients), or referred pain (2 patients). The cause of nociceptive pain was secondary to tumor recurrence in 16 patients and secondary to benign inflammation in 3 patients. Of the six (23%) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…This type of pain is histologically related to infi ltration of the peripheral nerves and nociceptive receptors by the cancer. 15 Cancer with a high grade in the histological mode of invasion such as YK-4 may directly stimulate the peripheral nerve endings and nociceptive receptors. Oral cancer pain may result from the dense distribution of trigeminal nerve invasion of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of pain is histologically related to infi ltration of the peripheral nerves and nociceptive receptors by the cancer. 15 Cancer with a high grade in the histological mode of invasion such as YK-4 may directly stimulate the peripheral nerve endings and nociceptive receptors. Oral cancer pain may result from the dense distribution of trigeminal nerve invasion of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,15,18 Epstein and Stewart 5 reported that pain was present at the time of diagnosis in 82% of 31 patients with head, neck, or oropharyngeal cancer. Cuffari et al 3 reported that about 67% of patients awaiting treatment for oral cancer complain of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Severe, progressive posttreatment pain associated with occult recurrent tumors is not uncommon. Recurrence pain is typically located near the tumor site and continuous in temporal pattern [15]. In addition, a neuropathic "shooting" quality is frequently reported by patients with tumor recurrence pain [19•].…”
Section: Pain Related To Recurrence Of Cancermentioning
confidence: 99%
“…The most common causes of this syndrome are the "extracranial" etiologies, with maxillary sinus, pharyngeal, laryngeal, and oral cavity tumors being the most frequent diagnoses [16]. Despite cancer being an uncommon cause of cranial nerve palsies, this scenario is not uncommon in patients with head and neck cancer.…”
Section: Cervicofacial Painmentioning
confidence: 99%
“…Despite cancer being an uncommon cause of cranial nerve palsies, this scenario is not uncommon in patients with head and neck cancer. Headache, neuropathic facial pain characteristic of the nerve distribution, and neurologic deficits are the most common manifestations of these syndromes [16,17].…”
Section: Cervicofacial Painmentioning
confidence: 99%